2019
DOI: 10.2352/issn.2169-2629.2019.27.4
|View full text |Cite
|
Sign up to set email alerts
|

Time course of chromatic adaptation under dynamic lighting

Abstract: Chromatic adaptation is an extensively studied concept. However, less is known about the time course of chromatic adaptation under gradually-changing lighting. Two experiments were carried out to quantify the time course of chromatic adaptation under dynamic lighting. In the first experiment, a step change in lighting chromaticity was used. The time course of adaptation was well described by the Rinner and Gegenfurtner slow adaptation exponential model [Vision Research, 40(14), 2000], and the adaptation state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They found that the slow phase had a half-life of about 20s and adaptation had reached steady state within 2 minutes. Spieringhs et al [5] confirmed Rinner's conclusions. Their experimental results of time course chromatic adaptation could be fitted using Rinner's slow adaptation exponential model [3].…”
Section: Introductionmentioning
confidence: 69%
“…They found that the slow phase had a half-life of about 20s and adaptation had reached steady state within 2 minutes. Spieringhs et al [5] confirmed Rinner's conclusions. Their experimental results of time course chromatic adaptation could be fitted using Rinner's slow adaptation exponential model [3].…”
Section: Introductionmentioning
confidence: 69%
“…Rinner and Gegenfurtner [4] also used the adjustment method to obtain an achromatic appearance. Later, Spieringhs et al [5] used two methods, the method of adjustment and the method of constant stimuli. They reported that the difference in time constant would be influenced by the psychophysical methods.…”
Section: Introductionmentioning
confidence: 99%
“…The time course of chromatic adaptation is also typically measured as the time for color appearance to stabilize after an abrupt change, rather than the phase lag in following smooth changes. A recent study (Spieringhs, Murdoch, & Vogels, 2019) directly compared adaptation progression following abrupt versus smooth changes, and found distinct time constants for the two. After abrupt changes, although most compensation occurs within the first minute of illumination swap (Fairchild & Lennie, 1992;Fairchild & Reniff, 1995) it might take up to 5 minutes to reach full stabilization of color appearance (Gupta et al, 2020;Hunt, 1950;Jameson, Hurvich, & Varner, 1979).…”
Section: Introductionmentioning
confidence: 99%